Sectional generator thermoelements in a magnetic field - Konstantynovych, I.A.; Kuz, R.V.; Makhanets, O.M.; Cherkez, R.G. (Journal of Thermoelectricity, 2023)
Using computer simulation, temperature distributions in the working body of sectional thermoelements in a magnetic field were determined. Temperature dependences of the efficiency of sectional gyrotropic thermoelements were found. It was established that the efficiency of generator gyrotropic sectional thermoelements depends on the number of sections. Bibl. 14, Figs. 4.